Hydatic thyroid cyst - Latourrette, Federico; Liard, Washington (Cirugía del Uruguay, 2020)
We present the case of a 67-year-old woman with a hard nodule in the right lobe of the thyroid, without regional or general repercussions, which raised the clinical suspicion of neoplasma. Puncture of the tumor allowed the extraction of rock crystal fluid, which changed the diagnostic orientation towards the possibility of a parathyroid cyst or cyst hydatid. The paraclinical studies carried out were not explanatory, so the intervention was considered, performing subtotal thyroidectomy, which showed that it was a hydatid thyroid cyst, which was confirmed by the histological study. A review of the national bibliography will be carried out, finding seven other similar observations